La práctica del teatro como experiencia colaborativa para fortalecer la convivencia escolar (2019)
This thesis deals with the problem of school coexistence inside and outside the classroom from an improvement perspective using mediation the practice of theater as a collaborative experience for the improvement of school coexistence in the Technical EI Francisco de Paula Santander de Soledad taking as an experiment the 6th grade students.